The family of the 21st century and the influence on the child’s school performance - Sandu, Mihaela Luminița; Stefana Mirela, Ivanciu (Technium Social Sciences Journal, 2023)
From a sociological perspective, „the family is a relatively permanent social group of individuals linked to each other by blood, origin, marriage or adoption, who share primary responsibility for the reproduction and care of members of society. The family is the fundamental instrumental core of the broader social structure, in the sense that all other institutions depend on its influences.” The family is also referred to as the foundation of society, later becoming a factor of social stability, being responsible for the tone it gives in relation to society, its stability also determining the stability of society. The way in which the family influences the development of children is complex and research can determine the effects of specific characteristics of parents in learning specific characteristics in children. The family climate is very important in determining educational influences and is a major role in the growth and education of the child and adolescent.